2010
DOI: 10.1590/s1516-44462010000400011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of executive functions in obese individuals with binge eating disorder

Abstract: OBJECTIVE: The aim of this study was to assess executive functions of obese individuals with binge eating disorder. METHOD: Thirty-eight obese individuals with binge eating disorder were compared to thirty-eight obese controls without binge eating disorder in terms of their executive functions. All individuals were assessed using the following instruments: Digit Span, Trail Making Tests A and B, Stroop Test and the Wisconsin Card Sorting Test. In addition, four subtests from the Behavioral Assessment of the Dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 26 publications
4
50
1
2
Order By: Relevance
“…Whereas certain previous studies (Davis et al, 2010; Duchesne et al, 2010; Wu et al, 2013) have excluded participants based on the presence of numerous conditions that may also affect neurocognitive functioning (e.g., history of major depression, borderline personality disorder, diabetes), the current study discounted participation based on a fewer number of conditions, most of which were strongly relevant to neurocognitive functioning (e.g., history of neurological disorders or a head injury). Thus, although the current sample may better reflect the broader population of bariatric surgery patients, findings regarding changes in cognitive functioning related to BED status may have been influenced by these comorbid conditions at baseline or by changes in these conditions during the follow-up period.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Whereas certain previous studies (Davis et al, 2010; Duchesne et al, 2010; Wu et al, 2013) have excluded participants based on the presence of numerous conditions that may also affect neurocognitive functioning (e.g., history of major depression, borderline personality disorder, diabetes), the current study discounted participation based on a fewer number of conditions, most of which were strongly relevant to neurocognitive functioning (e.g., history of neurological disorders or a head injury). Thus, although the current sample may better reflect the broader population of bariatric surgery patients, findings regarding changes in cognitive functioning related to BED status may have been influenced by these comorbid conditions at baseline or by changes in these conditions during the follow-up period.…”
Section: Discussionmentioning
confidence: 92%
“…Evidence supports the presence of deficits in neurocognitive performance across multiple domains in both obesity (Kerwin et al, 2010; Wolf et al, 2007) and eating disorders (Lena et al, 2004), including some mixed evidence for BED (Davis et al, 2010; Duchesne et al, 2010; Manwaring et al, 2011; Svaldi et al, 2010; Wu et al, 2013). As hypothesized, participants as a whole displayed significant improvements in test performance from pre-surgery baseline to post-surgery follow-up across three of four cognitive domains: attention, executive function, and memory; improvements were not seen in the domain of language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, cognitive flexibility (i.e., an individual’s ability to shift cognitive set and generate alternative strategies that are adaptive long term) has been associated with BED, but less so when relevant covariates are controlled (3, 710). Second, inhibitory control problems (i.e., poor ability to inhibit prepotent responses) may increase responsivity to potential internal and external cues (11); however, only three (10, 12, 13) of six studies (8, 10, 1214) have detected poorer inhibitory control in BED samples compared to controls. Third, poor decision-making (i.e., taking unnecessary risks, and prioritizing short-term reward over long-term goals) may underpin the tendency to binge eating for short-term comfort, without forethought to the long-term consequences (e.g., weight gain, feelings of guilt).…”
Section: Executive Function and Binge Eatingmentioning
confidence: 99%
“…Fourth, deficits in problem solving could lead to an inability to optimally generate and select a sequence of specific strategies to achieve a specific goal (e.g., planning meals so not to experience extreme hunger). Two studies have reported problem-solving deficits in those with BE (8, 10). Lastly, poor working memory (i.e., the ability to keep goal-relevant information in mind in the face of distractors) could predispose an individual to let self-regulative goals be overcome by cues (18).…”
Section: Executive Function and Binge Eatingmentioning
confidence: 99%